DAMPAK KENAIKAN HARGA MINYAK GORENG TERHADAP ALOKASI KEUANGAN RUMAH TANGGA WARGA DESA MUGO RAYEUK - Khatijah, K; Setiyana, Rusma (Fakultas Ekonomi Universitas Warmadewa, 2024)
This study aims to find out how the impact of rising cooking oil prices on financial allocations for residents of Dega Mugo Rayeuk whose income is below the minimum wage. This study also identifies what obstacles are faced by housewives in allocating their finances. This study uses a research method with a qualitative approach, where the research subjects are residents of the village of Mugo Rayeuk and the collection techniques used are village documents and interviews. Then the data is analyzed using percentages. The results of the analysis show that 66.66% of the residents of Mugo Rayeuk village experienced the impact of the increase in cooking oil prices. There are several obstacles faced by housewives in allocating their finances, namely uncertain income, income that is relatively small and below the minimum wage, and unstable prices of basic commodities, making it difficult for people to allocate their finances and also find it difficult to adjust income with expenses because the price of basic goods unstable and constantly increasing.